Phytochemical screening, investigation of the antisalmonella, antishigella, and antioxidant properties of the leaves of Rauvolfia vomitoria Afzel - Noudamadjo, Amandine; Goueti, Basile; Atchade, Bardieu; Djouonzo Toukam, Paul; Gbenou, Joachim; Glinma, Bienvenu; Kpadonou-Kpoviessi, Bénédicta; Dossou Sika KPOVIESSI, Salomé (Chemistry Department, The University of Brawijaya, 2024)
Rauvolfia vomitoria is a plant acclimatized in Benin - Africa that people use to treat several illnesses such as malaria, cough, typhoid fever, madness, toothache, diabetes, and nausea. The most used organs are leaves, stems, and roots. Thus, the purpose of this work is to contribute to the valorization of R. vomitoria by chemical and biological studies of this plant. Phytochemical analyses of the powder extracts were performed and revealed the presence of alkaloids, tannins, flavonoids, anthocyanins, saponins, terpenes, coumarins, mucilages, reducing compounds, free anthracene derivatives, bound anthracene derivatives (O-glycosides and C-glycosides) with absence of leuco-anthocyanins, quinone derivatives, steroids and cardiotonic glycosids. Evaluation of antisalmonella and antishigella properties of ethanol-water (70:30; V/V) and ethanolic extracts of R. vomitoria leaves showed minimum inhibitory concentrations (MIC) greater than 2000 µg.mL-1 against Salmonella and Shigella strains. The ethanolic extract was the most active by ABTS and FRAP methods and had very good antioxidant activity at scavenging concentration (SC50) equal to 138,62 µg.mL-1 and 185,99 µg.mL-1 respectively